2011
DOI: 10.1007/s10529-011-0769-3
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a chloroplast-localized small heat shock protein OsHSP26 confers enhanced tolerance against oxidative and heat stresses in tall fescue

Abstract: Small heat shock proteins are involved in stress tolerance. We previously isolated and characterized a rice cDNA clone, Oshsp26, encoding a chloroplast-localized small heat shock protein that is expressed following oxidative or heat stress. In this study, we transferred this gene to tall fescue plants by an Agrobacterium-mediated transformation system. The integration and expression of the transgene was confirmed by PCR, Southern, northern, and immunoblot analyzes. Compared to the control plants, the transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 22 publications
3
63
0
Order By: Relevance
“…Many studies have suggested that HSP21 plays an important role in protecting the thermolabile photosystem II (PSII) against heat stress (Heckathorn et al, 1998;Wang and Luthe, 2003;Shakeel et al, 2011). Several studies have also demonstrated that HSP21 protects PSII against oxidative stress (Härndahl et al, 1999;Kim et al, 2012). In addition, HSP21 has been suggested to have a dual role: protecting PSII from oxidative stress and promoting color changes during fruit maturation in tomato (Solanum lycopersicum; NetaSharir et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have suggested that HSP21 plays an important role in protecting the thermolabile photosystem II (PSII) against heat stress (Heckathorn et al, 1998;Wang and Luthe, 2003;Shakeel et al, 2011). Several studies have also demonstrated that HSP21 protects PSII against oxidative stress (Härndahl et al, 1999;Kim et al, 2012). In addition, HSP21 has been suggested to have a dual role: protecting PSII from oxidative stress and promoting color changes during fruit maturation in tomato (Solanum lycopersicum; NetaSharir et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Overproduction of the cytosolic class II sHSP At-HSP17.6A increased salt and drought tolerance (Sun et al 2001). Heterologous expression of OsHSP26 enhanced tolerance against oxidative and heat stresses in transgenic tall fescue and suggested a role of OsHSP26 in protecting photosystem II (PSII) from heat and oxidative stress (Kim et al 2012). In tobacco, constitutive expression of the tomato mitochondrial small heat shock protein enhanced thermotolerance in transgenic plants (Sanmiya et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Photosystem II (PS II) is one of the most labile protein complexes that are affected by abiotic stress [6]. sHSPs function in the protection of PS II during heat stress [2,7] and cold stress [8]. The chloroplast is one of the major sites for the generation of ROS during normal photosynthetic electron transfer, and the increase in ROS generation during stress adversely affects several macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…The chloroplast is one of the major sites for the generation of ROS during normal photosynthetic electron transfer, and the increase in ROS generation during stress adversely affects several macromolecules. There is emerging evidence that oxidative stress increases the expression of sHSP genes [7,9]. Conceivably, sHSP26 might be involved in oxidative stress tolerance.…”
Section: Introductionmentioning
confidence: 99%